Investigation of characteristics of drain systems of rapid filters on water treatment plants - Sorokina, Kateryna (Technology audit and production reserves, 2019)
The object of research is the modern design of drainage systems of rapid filters. The drainage distribution system of rapid filters is their most important element, which determines the uniformity of filtrate collection and its quality, as well as the distribution of washing water and overall filter washing efficiency. An analysis of the results of the reconstruction of filter drainage systems at the Dnipro water treatment complex of the Kharkivvodokanal utility company (Ukraine) is carried out. The analysis of operational indicators of the use of drainage systems of rapid filters carried out in the work reveals the feasibility of their use. Technical characteristics and operating experience shows that the systems made of polymer concrete are the most promising. Existing technologies make it possible to obtain porous polymer concrete of the optimal composition both in the factory and directly at the facility. Silica sand is used as a filler – grains with a size of 0.6–1.2 mm, which have a shape close to spherical (rounded). Each grain is covered with a layer of polymer binder, when connecting the grains intergranular structural bridges are formed. After completion of the polymerization process, a material with a regular structure with an extensive network of pore channels is formed. The high smoothness of the channels, as a result of coating with a polymer film, provides low values of hydraulic resistance of the filter materials. Timeliness and completeness of the regeneration of the filter provides a given service life. Otherwise, a gradual increase in the hydraulic resistance of the filter is possible, which in the future can no longer be reduced even by high-intensity washing through contaminants in the pore channels. This will lead to the need for early replacement of filter elements. The use of polymer-concrete drainage systems will make it possible to abandon the gravel layers that support, avoid clogging the drainage, reduce the consumption of flushing water and water for own needs in general, and reduce energy consumption.